The relationship between multiple plasma biomarker levels and renal disease activity in Fabry disease - Seyda Gul Ozcan; Necmi Eren; Mevlut Tamer Dincer; Zeynep Atli; Murat Bolayirli; Metin Ergul; Hakan Ozer; Kultigin Turkmen; Sinan Trabulus; Nurhan Seyahi (BMC Nephrology)
Abstract Background Fabry disease is a rare lysosomal storage disorder. The genotypic and phenotypic heterogeneity of the disease complicates the prediction of disease activity. This study aimed to evaluate the association between multiple plasma biomarkers and disease activity in Fabry disease. Methods A cross-sectional analysis was conducted involving 87 Fabry patients, 46 chronic kidney disease (CKD) patients, and 41 healthy controls. Plasma levels of KIM-1, MCP-1, YKL-40, TNFR-1, TNFR-2, and cystatin-C were measured using ELISA. eGFR was calculated using creatinine and creatinine-cystatin C-based CKD-EPI formulas. Fabry patients on renal replacement therapy were analyzed as a subgroup. Primary analyses focused on 62 Fabry patients receiving enzyme replacement therapy. Results Although eGFR (cr) did not differ significantly between Fabry patients and healthy controls, eGFR(cr-cys) was significantly lower in Fabry patients. After adjusting for age, gender, and BMI, MCP-1 and TNFR-2 levels were significantly lower in Fabry patients than in CKD patients. Among Fabry patients, those with renal involvement, had significantly higher MCP-1 levels than those without. While KIM-1 and YKL-40 did not differ significantly between groups, both were significantly elevated in patients with Lyso-Gb3 > 4 ng/mL and positively correlated with Lyso-Gb3. Conclusion MCP-1, TNFR-2, YKL-40, and cystatin C may serve as potential biomarkers for different aspects of Fabry disease activity. Further investigation into the associated pathogenic pathways may support the development of novel diagnostic tools or targeted therapies.